Solid-state anaerobic digestion of sweet corn waste: The effect of mixing and recirculation interval - Nirunsin, Rotjapun; Saipa, Sasithorn; Sawatdeenarunat, Chayanon (Center of Biomass & Renewable Energy (CBIORE), 2024)
The mixing and sludge recirculation interval is one of the key successes of the solid-state anaerobic digestion process, a promising technology for converting high-solid agro-industrial wastes to renewable energy. This study employed a pilot-scale completely stirred tank reactor to examine biogas production from sweet corn waste, including corn cobs, husks, and seeds. The reactor was operated as solid-state anaerobic digestion at an ambient temperature. The mixing and recirculating intervals were set to non-mixing and mixing for 10 minutes every 3, 6, and 12 hours. The initial total solid of the feedstock was 25%, while the hydraulic retention time was 30 days. The results showed that during the mixing and recirculation every three hours, the highest chemical oxygen demand, total solid, and volatile solid (VS) removal efficiencies were 85.42%, 62.92%, and 64.59%, respectively. The ratio between volatile fatty acid and alkalinity ranged between 0.20 and 0.30 without any sign of system failure. The highest specific methane yield of 766 L/kg VSadded was obtained in the experiment with mixing and recirculating intervals every 3 hours. It was found that the modified Gompertz model could effectively fit the methane yields with an R2 of 0.9667. The modeled methane production potential and the maximum methane production rate were 867.40 NL/kg VSadded and 132.01 NL/kg VSadded-d, respectively. Additionally, the levelized cost of the biogas produced from the solid-state anaerobic digestion of the sweet corn waste was calculated to be 0.61 USD/kg. The findings of this study can serve as a guide for the design and operation of the SS-AD system, which aims to transform various types of lignocellulosic waste into environmentally friendly energy.